Role of energy storage in residential energy demand decarbonization: system-level techno-economic comparison of low-carbon heating and cooling solutions - Aunedi,M; Olympios,AV; Pantaleo,AM; Mersch,M; Markides,CN (2023)
This paper explores various combinations of electric heat pumps (EHPs), hydrogen boilers (HBs), electric boilers (EBs), hydrogen absorption heat pumps (AHPs) and energy storage technologies (electric and thermal) to assess their potential for matching heating and cooling demand at low cost and with low carbon footprint. Thermodynamic and component-costing models of various heating and cooling technologies are integrated into a whole-energy system cost optimisation model to determine cost-effective configurations of heating and cooling systems that minimise the overall investment and operation cost for both the system and the end-user. Case studies presented in the paper focus on two archetypal systems that differ in terms of heating and cooling demand and availability profiles of solar and wind generation. The proposed approach quantifies how the cost-efficient portfolios of low-carbon heating and cooling solutions are driven by the characteristics of the system such as share of variable renewables or heating and cooling demand. Modelling results suggest that capacity choices for heating and cooling technologies will vary significantly depending on system properties. More specifically, air-to-air EHPs, with their cost and efficiency advantages over air-to-water EHPs, could make a significant contribution to low-carbon heat supply as well as cooling, although their contribution may be constrained by the compatibility with existing heating systems. They are found to be a useful supplementary source of space heating that is able to displace between 20 and 33 GWth of capacity of other heating technologies compared to the case where they do not contribute to space heating.